Unusual localization of osteoid osteoma at the physis of the proximal femur - Mohammad Al Nawaiseh, MD; Jehad F. AlSamhori, MD; Jawad K. Al Shawabkeh, MD; Omar M. Albtoush, MD; Omar Q. Samarah, MRCSI (Radiology Case Reports)
In the current analysis we describe a case of osteoid osteoma located at the physis of the right femoral capitis of a 5-year-old male patient. This case represents a rare location for this benign tumor which commonly encountered at the shafts of the long bones in young patients. Patient's presentation was unique from the classical symptoms of osteoid osteoma. Diagnostic workout has been thoroughly described. Treatment was performed successfully with minimally invasive microwave ablation with full recovery. This case highlights the potential cause of hip pain in the current unusual location and underscores the current uncommon presentation in young patients.